Production of Healthy Sugar by Adding Winter Melon [Benincasa hipsida (Thunb.) Cogn.] From Coconut Sap - Megasari, Gabrilla Ulfa; Fahmi; Nurkhamidah, Siti (Eksergi, 2025)
The increasing prevalence of health issues such as diabetes, obesity, and hypertension due to excessive sugar consumption has prompted the need for healthier sugar alternatives. This study investigates the production of healthy sugar using coconut sap enriched with winter melon (Benincasa hispida) extract, which offers various health benefits, including anti-diabetic properties. The production process employed a vacuum rotary evaporator at controlled temperatures (50–80°C) to preserve the nutritional and physical qualities of the sugar while minimizing adverse effects of traditional methods. The study assessed sugar composition, crystallization behavior, and product yield. Results showed that the addition of winter melon extract enhanced antioxidant properties and functional value, while varying sugar seed concentrations improved crystallization, yield (up to 10.48%), and color stability. This research contributes to developing low-glycemic, nutritious sugar alternatives, meeting the increasing demand for healthier sweeteners.